Problem Based Learning in Medical Education - Mansur, DI; Kayastha, SR; Makaju, R; Dongol, M (Kathmandu University Medical Journal, 2014)
Problem based learning, originally introduced in the Medical School at Mc- Master University in Canada in the late 1960s, and is now being used as a learning method in many medical schools in the United Kingdom and worldwide. Problem based learning have been adapted in many medical colleges of Nepal be used either as the mainstay of an entire curriculum or for the delivery of individual courses. Institution of Medicine, Tribhuvan University in 1980, BP Koirala Institute of Health Sciences at Dharan in 1999, KUSMS with the great support of faculties from Harvard University in 2001, Patan Academy of Health Sciences (PAHS), and lately all the affiliated medical colleges of Kathmandu University have adapted Problem based learning DOI: http://dx.doi.org/10.3126/kumj.v10i4.11002 Kathmandu Univ Med J 2012;10(4):78-82